The Use of Snake and Ladders Game to Improve Mathematics Outcomes and Student Engagement in Primary Schools - Novia Rohmadona; Sigit Dwi Laksana; Devid Dwi Erwahyudin (UIN Sunan Gunung Djati Bandung, 2026)
The low ability of students at SDN 2 Kauman Ponorogo in learning mathematics often becomes a challenge that affects the effectiveness of the learning process. Many students consider mathematics to be one of the difficult and boring subjects. To address this, Snake and Ladders was introduced as a game-based media capable of creating an active and interactive learning process. This study aims to describe the implementation of the Snake and Ladders games in mathematics learning and to analyze its effect on improving learning outcomes as well as the active involvement of fifth-grade students at SDN 2 Kauman Ponorogo. This study uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation, and the research subjects consist of 2 teachers and 14 fifth-grade students. Data analysis was conducted using the Miles, Huberman, and Saldana model, which includes data condensation, data collection, data display, drawing conclusions systematically, and verification. The research results showed an increase in active participation and student learning outcomes after using the Snake and Ladders games as a medium in mathematics learning. This improvement is indicated by the rising trends in students' learning outcome scores as well as positive changes in the active participation table. These findings are supported by observations and interviews showing that students are more enthusiastic and can easily understand the material. Therefore, the Snake and Ladders game can be used as an alternative innovative learning medium to create an active and interactive mathematics learning environment in primary schools.